Effect of milling time on the formation of carbon nanotube by mechano-thermal method - Evin, Ertan; Guler, Omer; Aksoy, Mustafa; Guler, Seval Hale (Indian Acad Sciences, 2015)
Mechano-thermal method was used for synthesizing the carbon nanotubes (CNTs) in this study. In this method, graphite powders in the elemental form were firstly exposed to milling process in high-energy ball milling and then the milled powders were annealed at high temperatures. As a result of milling of the graphite, ultra-active disordered carbon structures were obtained. This structure serves as a carbon source for the formation of nanotubes during the annealing process. This study investigated the effect of the milling process. For this purpose, graphite powders were milled at different periods such as 5 and 150 h and then annealed at 1600 C-A degrees. The transmission electron microscopy and scanning electron microscopy examinations demonstrated that CNTs formed in samples milled both for 5 and 150 h. However, the difference in the milling time influenced the amount of CNTs, their size and the formation of other structures except from nanotubes.
Keywords: Carbon nanotubes; mechano-thermal process; ball milling time